Earlier contact with child protection services among children of parents with criminal convictions and mental disorders - Whitten, Tyson (Child maltreatment, 2021)
Parental history of offending and/or mental illness are risk factors for child maltreatment. However, limited research has directly contrasted the role of maternal versus paternal criminal offending or mental health problems in contributing to earlier contact with the child protection system. In this study we examined the relative contributions of these risk factors in relation to the time to the offspring’s first report to child protection services, or first placement in out of home care (OOHC), using administrative records for a population sample of 71,661 children. Prior paternal offending had a greater independent effect on time to the offspring’s first contact with child protection services (HR = 2.27 [95% CI = 2.14-2.40]) than maternal offending (HR = 1.75 [95% CI = 1.63 -1.87]) or maternal mental disorder diagnosis (HR = 1.66 [95% CI = 1.57 -1.77]). By contrast, prior maternal offending (HR = 2.58 [95% CI = 2.26-2.95]) and mental disorder diagnosis (HR = 2.33 [95% CI = 2.05-2.63]) had a greater effect on earlier placement in OOHC, relative to prior paternal offending (HR = 1.59 [95% CI = 1.35 -1.88]) and mental disorder diagnosis (HR = 1.06 [95% CI = 0.94 -1.19]). These findings demonstrate the potential benefits of coordinated government responses across multiple agencies to identify vulnerable children and families who might benefit from early interventions or support services.